Pagbabaybay at pagtutumbasan ng mga katawagang pangkomersyo - Lanuza, Evelyn Andrada (Leyte-Samar Studies, 1989)
"This study tried to determine the perception of seventy seven (77) direct service workers, social workers and welfare aides-of the Ministry of Social Services and Development in Regions V, VIII and IX regarding development by analyzing the social problems they deal with like those associated with the delivery of social services and the approaches they adopt to minimize the problems. The study tried to identify the common viewpoints an differences between the social worker and the welfare aide regarding development."